PERANAN GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA DI BAMRUNG ISLAM SCHOOL PHATTALUNG, THAILAND SELATAN - Az-zahra, Jihan; Zailani, Zailani (IAIN Bone, 2024)
International Real Work Lecture (KKNI) provides a perspective on the role of educators in improving the ability to read the Al-Qur’an at Bamrung Islamic Academy in Phattalung, Southern Thailand. Al-Qur'an education occupies an important position in Islamic Religious Education. Students need guidance from educators to understand the Al-Qur’an. Educational institutions such as the Bamrung Islamic Academy in Phattalung are one of the places to get Al-Qur'an education. This research adopts a qualitative field approach. Through KPLI at Bamrung Islamic Academy, researchers gained experience in assisting students in reading the Al-Qur'an, understanding the principles of recitation, so that students can easily understand and read the Al-Qur'an. Educators have an important role in helping students overcome difficulties in reading the Al-Qur’an.